Analysis of Energy Transmission for Inductive Coupled RFID Tags - Scholz, Peter; Reinhold, Christian; John, Werner; Hilleringmann, Ulrich (2007 IEEE International Conference on RFID)

"Das Reich Gottes lässt sich nicht ertanzen" (Heinz Zahrnt). 6 Auftakte zum Verhältnis von Tanz und Religion - Schroeter-Wittke, Harald (Tanz und Religion. Theologische Perspektiven)

Bestürzende Frömmigkeit. Ein Magnificatgottesdienst am Abend des 3. Advents. Luk 1,46-55 / J.S. Bach: Magnificat BWV 243 - Schroeter-Wittke, Harald (Junge Kirche)

Tanz und Religion. Theologische Perspektiven. Helga Kuhlmann zum 50. Geburtstag

Theologie und Kreativität. Improvisationen zwischen Wort und Klang - Schroeter-Wittke, Harald (Wissen im Alter hat Zukunft - Kreativität im Alter)

Evangelisches Paderborn. Protestantische Gemeindegründungen an Pader und Weser

Spielen & Improvisieren - Schroeter-Wittke, Harald (Christliche Lebenskunst)

Kleines Kabarettistisches Kirchenjahr

Trinitatis. 2. Kor. 13.11(12)13: Aller guten Dinge sind drei, oder: Von der Mediation zur Meditation - Schroeter-Wittke, Harald (Göttinger Predigtmeditationen)

Paradise now - Paradiesklänge von Bach bis Berg - Schroeter-Wittke, Harald (Magazin für Theologie und Ästhetik. http://www.theomag.de/52/hsw10.htm)

12. Sonntag nach Trinitatis. 1. Korinther 3,9-15: Kein Spiel mit dem Feuer - Schroeter-Wittke, Harald; Kirsner, Inge (Predigtstudien VI/2)

Generation and Time-Resolved Detection of Coherently Controlled Electric Currents at Surfaces - Güdde, J.; Rohleder, M.; Meier, Torsten; Koch, S.W.; Höfer, U. (Frontiers in Optics 2008/Laser Science XXIV/Plasmonics and Metamaterials/Optical Fabrication and Testing)

Ultrafast Dynamics of Optically-Induced Charge and Spin Currents in Semiconductors - Meier, Torsten; Duc, Huynh Thanh; Vu, Quang Tuyen; Pasenow, Bernhard; Hübner, Jens; Chatteryee, Sangam; Rühle, Wolfgang W.; Haug, Hartmut; Koch, Stephan W. (Advances in Solid State Physics)
The ultrafast dynamics of optical excitations in semiconductors and semiconductor nanostructures can be computed on a microscopic theoretical basis using the semiconductor Bloch equations. This set of equations allows one to nonperturbatively evaluate light-field-induced intraband and interband excitations and is also well suited for the analysis of many-body effects such as excitonic resonances and carrier-carrier and carrier-phonon scattering processes. In this article we start with a description of an experimental observation of coherent spin photocurrents, then we briefly introduce the theoretical approach and review some results of our theory concerning the microscopic description of the ultrafast coherent optical generation and the temporal decay of charge and spin currents in semiconductor nanostructures. The computed transients show an enhanced damping of the spin current relative to the charge current as a consequence of Coulomb scattering between carriers with opposite spin. The influence of quantum kinetic memory effects on the dynamics of the photocurrents is analyzed by evaluating the scattering terms beyond the Markov approximation.

Ultrafast Dynamics of Optically-Induced Charge and Spin Currents in Semiconductors - Meier, Torsten; Duc, Huynh Thanh; Vu, Quang Tuyen; Pasenow, Bernhard; Hübner, Jens; Chatteryee, Sangam; Rühle, Wolfgang W.; Haug, Hartmut; Koch, Stephan W. (Advances in Solid State Physics)
The ultrafast dynamics of optical excitations in semiconductors and semiconductor nanostructures can be computed on a microscopic theoretical basis using the semiconductor Bloch equations. This set of equations allows one to nonperturbatively evaluate light-field-induced intraband and interband excitations and is also well suited for the analysis of many-body effects such as excitonic resonances and carrier-carrier and carrier-phonon scattering processes. In this article we start with a description of an experimental observation of coherent spin photocurrents, then we briefly introduce the theoretical approach and review some results of our theory concerning the microscopic description of the ultrafast coherent optical generation and the temporal decay of charge and spin currents in semiconductor nanostructures. The computed transients show an enhanced damping of the spin current relative to the charge current as a consequence of Coulomb scattering between carriers with opposite spin. The influence of quantum kinetic memory effects on the dynamics of the photocurrents is analyzed by evaluating the scattering terms beyond the Markov approximation.

Rabi flopping of charge and spin currents generated by ultrafast two-colour photoexcitation of semiconductor quantum wells - Pasenow, B.; Duc, H.T.; Meier, Torsten; Koch, S.W. (Solid State Communications)
Keywords: Materials Chemistry; Condensed Matter Physics; General Chemistry

Rabi flopping of charge and spin currents generated by ultrafast two-colour photoexcitation of semiconductor quantum wells - Pasenow, B.; Duc, H.T.; Meier, Torsten; Koch, S.W. (Solid State Communications)

Rabi flopping of charge and spin currents generated by ultrafast two-colour photoexcitation of semiconductor quantum wells - Pasenow, B.; Duc, H.T.; Meier, Torsten; Koch, S.W. (Solid State Communications)

High harmonics generated in semiconductor nanostructures by the coupled dynamics of optical inter- and intraband excitations - Golde, D.; Meier, T.; Koch, S. W. (Physical Review B)

Negotiating Development in Muslim Societies: Gendered Spaces and Translocal Connections

Women's Organisations and Social Transformation in Malaysia. Between Social Work and Legal Reform - Spiegel, Anna (Negotiating Development in Muslim Societies. Gendered Spaces and Translocal Connections)

Cluster tilting for one–dimensional hypersurface singularities - Burban, Igor; Iyama, O.; Keller, B.; Reiten, I. (Advances in Mathematics)

Maximal Cohen-Macaulay modules over surface singularities - Burban, Igor; Drozd, Yu. (Trends in Representations of Algebras and Related Topics)

Visuelle Wissenskommunikation in Astronomie und Nanotechnologie. Zur epistemischen Produktivität und den Grenzen von Bildern - Adelmann, Ralf; Hennig, Jochen; Heßler, Martina (Wissensproduktion und Wissenstransfer. Wissen im Spannungsfeld von Wissenschaft, Politik und Öffentlichkeit)

The visual potential of history. Images of the past in film, television and computer games - Adelmann, Ralf (Journal of Social Science Education)

Die 'weise Masse'. Zur medienökonomischen Ordnung des Politischen - Adelmann, Ralf (Ästhetik & Kommunikation)

Lotsen, Schlichten, Mediieren. Anregungen und Befunde zum Umgang mit Konflikten in der Schule - Freitag, Christine (Pädagogik, 60. Jg., Heft 07-08/2008)

Provokationen und Reaktionen: Homogenisierungsprozesse in international vergleichender Perspektive - Freitag, Christine (Lernarrangements für heterogene Gruppen)

Förderdiagnostik zwischen Selektion und Integration - Freitag, Christine; von Bargen, I.; Gorges, J. M.; Hollwedel, K.; Jacobsen, A.; Schmidt, N.; Seitz, S. (Jahrbuch 2008 Schulbegleitforschung. Bremen)

Medienverwendung im Unterricht - Herzig, Bardo (Lehrer-Schüler-Interaktion. Inhaltsfelder, Forschungsperspektiven und methodische Zugänge)

Schule und digitale Medien - Herzig, Bardo (Handbuch Medienpädagogik)

Digitale Medien in informellen und formalen Lernumgebungen von Kindern und Jugendlichen - Herzig, Bardo; Aßmann, S. (Neue Medien in der Bildung)

Entwicklung und Validierung eines Instruments zur Messung professioneller Handlungskompetenz bei (angehenden) Physiklehrkräften - Riese, Josef; Reinhold, Peter (Lehrerbildung auf dem Prüfstand)

A Newton-Multigrid algrithm for elasto-plastic/viscoplastic problems - Mahnken, Rolf (Computational Mechanics)
Keywords: Applied Mathematics; Computational Mathematics; Computational Theory and Mathematics; Mechanical Engineering; Ocean Engineering; Computational Mechanics

Professionelles Wissen und Handlungskompetenz angehender Physiklehrer - Riese, Josef; Reinhold, Peter (Kompetenzen, Kompetenzmodelle, Kompetenzentwicklung. Gesellschaft für Didaktik der Chemie und Physik. Jahrestagung in Essen 2007)

Reflexive interculturality as a development objective for schools and school sport - Grimminger-Seidensticker, Elke; Gieß-Stüber, P. (Sport - Integration - Europe. Widening Horizons in Intercultural Education)

Promoting intercultural competence in the continuing education of physical education teachers - Grimminger-Seidensticker, Elke (Sport - Integration - Europe. Widening Horizons in Intercultural Education)

Reflexive Interkulturalität als Schul(sport)entwicklungsperspektive - Grimminger-Seidensticker, Elke; Gieß-Stüber, P. (Sport - Integration - Europa. Neue Horizonte für interkulturelle Bildung)

Die Förderung interkultureller Kompetenz in der Sportlehrerfortbildung - Grimminger-Seidensticker, Elke (Sport - Integration - Europa. Neue Horizonte für interkulturelle Bildung)

Study structures for physical education teachers in comparison - Grimminger-Seidensticker, Elke (Sport - Integration - Europe. Widening Horizons in Intercultural Education)

(Sport-)Lehrerbildung im europäischen Vergleich - Grimminger-Seidensticker, Elke (Sport - Integration - Europa. Neue Horizonte für interkulturelle Bildung)

Kultur und Fremdheit als sportdidaktische Perspektive - Grimminger-Seidensticker, Elke; Gieß-Stüber, P. (Handbuch Sportdidaktik)

Sport - Integration - Europa. Bibliographie

Race and Ethnicity in colonial contexts - Schubert, Michael (A Historical Companion to Postcolonial Literatures in Continental Europe and its Empires)

Intelligenz und Bewegung - Tanz im Fokus der Kognitionswissenschaft - Güldenpenning, Iris; Lex, Heiko (Zeitschrift für Sportpsychologie)

EvAnT: Analysis and Checking of event traces for Wireless Sensor Networks - Woehrle, Matthias; Plessl, Christian; Lim, Roman; Beutel, Jan; Thiele, Lothar (IEEE Int. Conf. on Sensor Networks, Ubiquitous, and Trustworthy Computing (SUTC))
Keywords: WSN; testing; verification

A Hardware Accelerator for k-th Nearest Neighbor Thinning - Schumacher, Tobias; Meiche, Robert; Kaufmann, Paul; Lübbers, Enno; Plessl, Christian; Platzner, Marco (Proc. Int. Conf. on Engineering of Reconfigurable Systems and Algorithms (ERSA))

IMORC: An infrastructure for performance monitoring and optimization of reconfigurable computers - Schumacher, Tobias; Plessl, Christian; Platzner, Marco (Many-core and Reconfigurable Supercomputing Conference (MRSC))
Keywords: IMORC; IP core; interconnect

Preparing for the ‘real’ market: national patterns of institutional learning and company behaviour in the European Emissions Trading Scheme (EU ETS) - Engels, Anita; Knoll, Lisa; Huth, Martin (European Environment)
Keywords: Management; Monitoring; Policy and Law; Geography; Planning and Development

Emissionshandel aus soziologischer Sicht: Wer handelt eigentlich wie mit Emissionsrechten? - Knoll, Lisa; Huth, Martin (uwf UmweltWirtschaftsForum)

Construction and Applications of Identity-Based Encryption without Pairings - Schrieb, Jonas
Keywords: Diplomarbeit